1984
DOI: 10.1159/000172955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Verapamil and Nifedipine on Renal Function and Hemodynamics in the Dog

Abstract: This study evaluates the direct effects of verapamil (5 µg/kg/min) or nifedipine (0.32 µg/kg/min) when infused into one renal artery for 2 h. The role of calcium in the systemic and renal vascular effects of angiotensin II (1 µg/i.v.bolus) was examined in each period.Renal blood flow was increased 11% by verapamil and 29% by nifedipine. Unlike other vasodilators, these drugs markedly increased GFR (by 75% with verapamil and 50% with nifedipine), and both caused a profound natriuresis, which outlasted the renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…In one of these studies, 49 the increments in RBF, GFR, and U Nl were similar to those in the aforementioned studies in which blood pressure remained constant. However, in the two other studies, 3254 the decrease in systemic blood pressure was accompanied by natriuresis but no significant changes in RBF or GFR.…”
Section: Effects Of Calcium Blockers On Renal Hemodynamics and Renal supporting
confidence: 76%
“…In one of these studies, 49 the increments in RBF, GFR, and U Nl were similar to those in the aforementioned studies in which blood pressure remained constant. However, in the two other studies, 3254 the decrease in systemic blood pressure was accompanied by natriuresis but no significant changes in RBF or GFR.…”
Section: Effects Of Calcium Blockers On Renal Hemodynamics and Renal supporting
confidence: 76%
“…Ichikawa et al (4) found that verapamil markedly inhibits the ANG II-induced de creases in glomerular plasma flow and filtra tion coefficient. Nifedipine was reported to suppress the decreasing action of ANG II on renal blood flow (RBF) (5,6). Similar results were observed with other calcium channel blockers, such as diltiazem (7) and nitrendi pine (8).…”
Section: Nisoldipinesupporting
confidence: 60%
“…There are a number of reports which show that the calcium entry blocking drugs have an action on the kidney to increase the excretion of sodium and water in experimental animals (Bell & Lindner, 1984;Dietz et al, 1983;Johns, 1985) and man (Zanchetti & Leonetti, 1985). The exact way in which these compounds alter the reabsorption of sodium and water is not known, but it could result from their action on renal haemodynamics, to increase renal blood flow, or 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%